Effectiveness of ambon banana stem juice as immunostimulatory against Aeromonas hydrophila infections in catfish Clarias gariepinus - Astria, Qorie; Nuryati, Sri; Nirmala, Kukuh; Alimuddin, Alimuddin (Jurnal Akuakultur Indonesia, 2017)
ABSTRACT Outbreaks of infectious diseases due to Aeromonas hydrophila in catfish can cause high death rates (80–100%). Fish disease control can be done using phytopharmaceutical to prevent or treat diseases of fish. One of the phytopharmaceutical that known to prevent the fish diseases is ambon banana stem Musa cavendishii var. dwarf Paxton. This study was conducted to test the effectiveness of catfish immersion using banana stem juice as an immunostimulant against bacterial infections A. hydrophila. The observed parameters were a total performance of production, hematological test, and water quality. Immersion of catfish seeds with stem juice was performed at a concentration of 5 mL/L, 13 mL/L, and 21 mL/L for 30 minutes. Each treatment consisted of three replications. A  total of 15 fishes were immersed in 1.5 L water. At day-9 after immersion, fish was infected by A. hydrophila bacteria at a dose of 104 cfu/mL. The results showed that fish treated with banana stem juice at a concentration of 13 mL/L had the survival rate of 53.33±6.67% which is higher than positive control (33.33±6.67%). Based on hematology observations on the 3rd day post-challenge test (H12) with A. hydrophila, total erythrocytes, hemoglobin, total leukocytes, phagocytic activity, differential leukocyte, and lysozyme activity was highest in treatment13 mL/L. Lower feed conversion ratio (1.08±0.04) were also obtained in treatment 13 mL/L. Thus Immersion of seeds in stem juice can boost the immune system against infections A. hydrophila. Keywords: Aeromonas hydrophila, ambon banana stem juice, soaking, catfish, immune system  ABSTRAK Wabah penyakit akibat infeksi Aeromonas hydrophila pada ikan lele dapat menyebabkan tingkat kematian yang tinggi (80–100%). Penanggulangan penyakit ikan dapat dilakukan menggunakan fitofarmaka untuk mencegah ataupun mengobati penyakit ikan. Salah satu fitofarmaka yang dapat digunakan dalam upaya pencegahan penyakit ikan adalah batang pisang ambon lumut Musa cavendishii var. dwarf Paxton. Penelitian ini bertujuan untuk menguji efektivitas perendaman benih ikan lele dengan menggunakan air perasan batang pisang ambon sebagai imunostimulan terhadap infeksi bakteri A. hydrophila. Parameter yang diamati selama penelitian adalah kinerja produksi, uji hematologi dan pengukuran kualitas air. Perendaman benih ikan lele dengan air perasan  dilakukan pada konsentrasi 5 mL/L, 13 mL/L, dan 21 mL/L selama 30 menit. Pada hari ke-9 setelah perendaman, ikan diinfeksi bakteri A. hydrophila pada kepadatan 104 cfu/mL. Hasil penelitian menunjukkan bahwa perendaman ikan dengan air perasan pada konsentrasi 13 mL/L memiliki kelangsungan hidup yakni sebesar 53,33±6,67%, lebih tinggi bila dibandingkan dengan kontrol positif  (33,33±6,67%). Berdasarkan pengamatan pada uji hematologi hari ke-3 pascauji tantang (H12) dengan bakteri A. hydrophila, total eritrosit, hemoglobin, total leukosit, aktivitas fagositik, dan aktivitas lisozim tertinggi terdapat pada perlakuan konsentrasi 13 mL/L. Rasio konversi pakan yang rendah (1,08±0,04) juga terdapat pada perlakuan 13 mL/L. Hal ini menunjukkan bahwa perendaman benih ikan lele pada air perasan dapat meningkatkan sistem imun terhadap infeksi bakteri A. hydrophila. Kata kunci: Aeromonas hydrophila, air perasan batang pisang ambon, perendaman, ikan lele, sistem imun